Premenstrual syndrome and the possibility of herbal medicine - I V Kuznetsova; V V Dil (IP Berlin A.V., 2014)
Psychosomatic and behavioral changes before menstruation, perceived by the majority of women violate daily activities, relationships with the environment and quality of life, becoming a disease by the name of premenstrual syndrome (PMS). The etiology of PMS remains unclear and concise, universal diagnostic criteria are missing, which leads to the lack of effective diagnosis and therapy. Hormone therapy of the PMS is one of the leading methods to eliminate the symptoms that occur in the luteal phase, but it has some limitations, and sometimes causes side effects that negate the benefits of its application. Psychotropic drugs are the drugs of choice for premenstrual dysphoric disorder, but their long-term use is generally not recommended because of the possibility of addiction and the occurrence of adverse reactions. The research for relevant means of reducing the severity or eliminating the symptoms of PMS, not only among drugs, but also among the means of herbal medicine and non-drug methods of exposure remains important.